Catalytic hairpin assembly mediated liposome-encoded magnetic beads for signal amplification of peroxide test strip based point-of-care testing of ricin. Issue 90 (27th October 2020) - Ye, Qi Chao; Men, Chen; Li, Yuan Fang; Liu, Jia Jun; Huang, Cheng Zhi; Zhen, Shu Jun
Abstract : In this study, a point-of-care testing (POCT) method for the detection of ricin B-chain (RTB) using a commercial peroxide test strip (PTS) combined with signal amplification via glucose oxidase-loaded liposome and catalytic hairpin assembly (CHA) was reported. Abstract : Herein, we propose a new peroxide test strip (PTS) based point-of-care testing (POCT) method to detect ricin B-chain qualitatively and quantitatively by using catalytic hairpin assembly (CHA) mediated liposome-encoded magnetic beads for signal amplification. The sensitivity of this PTS based POCT method was improved significantly because it combined CHA signal amplification and liposome-based signal amplification.